Conversations with Maurice Durozier (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Interview with Maurice Durozier, one of the oldest actors of Théâtre du Soleil, having joined it in 1980 for the show Richard II. The meeting took place between October and December 2014, in a café near Cartoucherie, the group’s headquarters in Paris. In an unpretentious way, the conversation went through topics such as the transmission at Théâtre du Soleil, the preparation and training of the actor, working with the text and the life in a troupe.
Keywords: Théâtre du Soleil; Maurice Durozier; Actor